1999
DOI: 10.1211/0022357991776976
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Permeability of Insulin across the Rat Intestinal Membrane by Various Absorption Enhancers: Their Intestinal Mucosal Toxicity and Absorption-enhancing Mechanism of n-Lauryl-β-D-maltopyranoside

Abstract: We have examined the in-vitro permeability characteristics of insulin in the presence of various absorption enhancers across rat intestinal membranes and have assessed the intestinal toxicity of the enhancers using an in-vitro Ussing chamber method. The absorption enhancing mechanism of n-lauryl-beta-D-maltopyranoside was studied also. The permeability of insulin across the intestinal membranes was low in the absence of absorption enhancers. However, the permeability was improved in the presence of enhancers s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
56
0
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 136 publications
(59 citation statements)
references
References 24 publications
2
56
0
1
Order By: Relevance
“…15) This surfactant-induced change in intestinal permeability is correlated with acute epithelial damage, as evidenced by release of cellular components from damaged intestinal epithelium which is attributable to the surfactants. 16,17) On the other hand, the toxicity of Labrasol and Gelucire 44/14 is very low, with Labrasol especially being quite safe because of its LD 50 value of 22 g/kg in rats. In the present study, we first focused on the efficiency of Labrasol and Gelucire 44/14 to enhance the intestinal absorption of LMWH as a water-soluble and poorly absorbable drug.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15) This surfactant-induced change in intestinal permeability is correlated with acute epithelial damage, as evidenced by release of cellular components from damaged intestinal epithelium which is attributable to the surfactants. 16,17) On the other hand, the toxicity of Labrasol and Gelucire 44/14 is very low, with Labrasol especially being quite safe because of its LD 50 value of 22 g/kg in rats. In the present study, we first focused on the efficiency of Labrasol and Gelucire 44/14 to enhance the intestinal absorption of LMWH as a water-soluble and poorly absorbable drug.…”
Section: Discussionmentioning
confidence: 99%
“…18) Two 2-hydroxybenzoyl derivatives, SNAC having 8 carbon chain lengths and SNAD having 10 carbon chain lengths, have been developed by Emisphere Technology as synthesized delivery agents for UFH 2) and LMWH, 16) respectively. In those two derivatives, C8-C10 might be the most suitable carbon chain length to enhance the absorption of UFH as evidenced by an increase in APTT.…”
Section: Discussionmentioning
confidence: 99%
“…37) Our previous study also demonstrated that the transepithelial electrical resistance of Caco-2 cells and rat colonic membranes was reduced in the presence of various absorption enhancers. 38,39) Therefore, we examined the absorption enhancing mechanisms of these enhancers using this electrophysiological technique. The present study showed that the Rm value at a steady state was about 700 W · cm 2 in the absence of absorption enhancers.…”
Section: Fig 3 Effects Of Various Absorption Enhancers On Rm Of Xenmentioning
confidence: 99%
“…Absorption enhancers have often been adopted to improve the absorption of poorly absorbable drugs, including hydrophilic antibiotics and peptide and protein drugs. These absorption enhancers include surfactants, bile salts, chelating agents, and fatty acids [Uchiyama et al, 1999;Yamamoto et al, 1996], Previous studies have indicated that there exists an almost linear relationship between the absorption-enhancing effects of some absorption enhancers in the small and large intestine and their membrane toxicities [Yamamoto et al, 1996]. Therefore, there is a need for the development of effective and less toxic absorption enhancers for use in clinical practice.…”
Section: Introductionmentioning
confidence: 99%